2018
DOI: 10.3390/biom8040169
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significance of Serum NEDD9 Levels in Patients with Pancreatic Cancer

Abstract: Introduction: Pancreatic cancer (PC) is a lethal malignancy. Various diagnostic, predictive, and prognostic biomarkers have been evaluated. This study was conducted to investigate the serum levels of neural precursor cell expressed developmentally downregulated protein 9 (NEDD9) in patients with PC and the relationship between tumor progression and known prognostic parameters. Materials and Methods: Serum samples were obtained on first admission before any treatment. Serum NEDD9 levels were determined using en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…Another study revealed that reduced expression of miR-451 increased chemoresistance in patients with metastatic castration-resistant prostate cancer by targeting NEDD9 [ 25 ]. Our work and other previous studies [ 13 , 27 , 28 ] have determined the role of NEDD9 in PAC. We show that high expression of NEDD9 is significantly correlated with clinical staging, lymph node metastasis, histologic stage, and significantly shorter survival time.…”
Section: Discussionsupporting
confidence: 60%
“…Another study revealed that reduced expression of miR-451 increased chemoresistance in patients with metastatic castration-resistant prostate cancer by targeting NEDD9 [ 25 ]. Our work and other previous studies [ 13 , 27 , 28 ] have determined the role of NEDD9 in PAC. We show that high expression of NEDD9 is significantly correlated with clinical staging, lymph node metastasis, histologic stage, and significantly shorter survival time.…”
Section: Discussionsupporting
confidence: 60%
“…Another study revealed that reduced expression of miR-451 increased chemoresistance in patients with metastatic castration-resistant prostate cancer by targeting NEDD9. 25 Our work and other previous studies 13,27,28 have determined the role of NEDD9 in PAC. We show that high expression of NEDD9 is signi cantly correlated with clinical staging, lymph node metastasis, histologic stage and signi cantly shorter survival time.…”
Section: Discussionmentioning
confidence: 57%
“…Esra Arslan 1 Hale Aral 2 Tamer Aksoy 1 Çiğdem Usul Afşar 3 Senem Karabulut 4 Fadime Didem Can Trabulus 5 Rıza Umar Gürsu 6 Tevfik Fikret Çermik 1 Scoring for HER2; • Score 0: negative immunostaining, • Score 1: poor staining/staining lesser than 30%, • Score 2: Uniform/complete membranous staining, even if weak staining, • Score 3: Uniform staining of at least 30%.…”
Section: Comparison Of Serum Nedd-9 Ca 15-3 and Cea Levels And Pet Me...mentioning
confidence: 99%
“…NEDD-9 overexpression has been reported to be strongly correlated with cancer metastasis due to its regulatory property on cell migration. [3][4][5] Carcinoembryonic antigens (CEA) and carbohydrate antigens 15-3 (CA 15-3) are used in BC follow-up; however, their prognostic value is limited regarding its sensitivity and specificity. 6 The American Society of Clinical Oncology does not recommend them for the diagnosis, screening, staging, and treatment follow-up of BC.…”
Section: Introductionmentioning
confidence: 99%